Present Status, Impact, and Challenges of Fish Farming at Bhaluka Upazila in Bangladesh - Shayla Sultana Mely; Md. Rony Babu; Abhishak Sarkar Joy; Md. Shahidul Islam; Md. Nazmul Hossen; Md. Rabiul Islam (Turkish Journal of Bioscience and Collections)
Objective: The current investigation was conducted to identify existing fish culture practise, livelihood condition of fish farmers, and the major challenges faced by fish farmers in Bhaluka upazila, Bangladesh.Materials and Methods: Data were collected through surveys, monitoring, and participatory rural appraisal (PRA) tools like focus group discussions (FGD), using a pre planned questionnaire survey. A group of 5 fish farmers was interviewed from each of the six villages.Results: In the study, majority of fish farmers were between the ages of 41 and 60 years. Fish farming was their major occupation; however, they did not receive any formal training in fish culture. Fish ponds were large (> 4000 m2) and medium in depth (1-2 m), and the most popular fish culture system was polyculture. Commercial feeds were used to supply nutrients, fertilisers (organic and inorganic) were also applied to the pond water to produce natural food. Salt, lime, zeolite, potassium permanganate, and oxygen tablets were used to maintain water quality. Epizootic ulcerative syndrome, argulosis, and tail and fin rot are most prevalent in the winter. Increasing feed costs, lack of financial support, and disease outbreaks were critical challenges in fish farming in the study area. The socioeconomic status of fish farmers was found to improve with fish farming.Conclusion: Fish farming substantially improved the livelihoods of fish farmers in the study area, despite many constraints. Government support, including microcredit support, the supply of high-quality inputs, including fish fry, feed, vaccinations, and the provision of training facilities could increase fish production in the region.